Association between epilepsy and risk of sexual dysfunction: A meta-analysis. (February 2019) - Zhao, Shankun; Tang, Zhen; Xie, Qiang; Wang, Jiamin; Luo, Lianmin; Liu, Yangzhou; Zhu, Zhiguo; Luo, Jintai; Zhao, Zhigang
Highlights: Both female and male patients with epilepsy are at risk of sexual dysfunction. Male epilepsy-patients had a higher risk of sexual dysfunction than female subjects. High prevalence of sexual dysfunction in patients with epilepsy may be multifactor. Sexual functioning assessment should be considered when treating epilepsy. Abstract: Purpose: Sexual functioning is an important factor influencing quality of life. Mounting evidence suggests that both male and female patients with epilepsy (PWE) have an increased risk of developing sexual dysfunction (SD). The aim of this meta-analysis was to quantify the association between epilepsy and the risk of SD. Methods: PubMed, Embase, and Cochrane Library database were systematically searched to identify the pertinent studies focusing on the association between epilepsy and SD. Relative risk (RR) for SD with 95% confidence interval (CI) was calculated. The overall quality of the evidence was generated by applying the GRADE-profiler. This meta-analysis was registered on the PROSPERO (ID: CRD42018103572, http://www.crd.york.ac.uk/PROSPERO ). Results: Nine studies (3 cross-sectional, 5 case-control, and 1 cohort) were included in this meta-analysis, for a total of 1556 subjects and 599 cases of epilepsy. Synthetic results demonstrated that epilepsy was associated with an increased risk of female SD (6 studies, pooled RR = 2.69, 95%CI: 1.48–4.89, P  =  0.001; heterogeneity: I 2  = 88.9%, P  <  0.001) as well as male SD (3 studies, pooled RR = 4.85, 95%CI: 2.01–11.7, P  <  0.001; heterogeneity: I 2  = 74.2%, P  =  0.021). The GRADE-profiler showed that the rate of events of SD on average in the PWE and the controls were 383/659 (58.1%) and 168/1017 (16.5%), respectively. The quality of evidence across outcomes was MODERATE. Conclusions: Epilepsy is significantly associated with an increased risk of SD in both sexes. These findings suggest that both clinicians and patients should recognize that epilepsy has a potential hazardous effect on sexual functioning.